Construal-level Mindsets Enhance Behavioral Persistence in Response to Incentive Valence - Kulkarni, Atul A.; Yuan, Hong (Journal of Behavioral Decision Making, 2017)
In this research, we find that incentive valence and construal-level mindsets can interact to influence behavioral persistence on challenging tasks. An abstract mindset improves persistence in response to positively framed incentives whereas a concrete mindset improves persistence in response to negatively framed incentives. This interaction effect can be observed even when the cues inducing construal-level mindsets are not related to the incentives or the incentivized tasks. Participants in our studies were either positively or negatively incentivized to solve a set of difficult anagrams, and were primed with an abstract or a concrete mindset using spatial (Study 1) and social (Study 2) cues. The participants persisted longer in response to the positively framed incentive when primed with spatially or socially remote cues. In contrast, for the negatively framed incentive, participants persisted longer when primed with spatially or socially proximal cues. Copyright © 2017 John Wiley & Sons, Ltd.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/bdm.2020
Keywords: construal-level; dept.mrk; incentive valence; mindset; persistence

Induction of Construal-Level Mindset via Experience of Surprise: An Abstract: Proceedings of the 2018 Academy of Marketing Science (AMS) Annual Conference | Request PDF - Kulkarni, Atul A.; Vanhamme, Joelle (ResearchGate, 2018)
Request PDF | Induction of Construal-Level Mindset via Experience of Surprise: An Abstract: Proceedings of the 2018 Academy of Marketing Science (AMS) Annual Conference | An experience of surprise is often an outcome of disconfirmation of expectations and can be associated with positive or negative affect depending... | Find, read and cite all the research you need on ResearchGate
Keywords: dept.mrk

Boomerang effect of incentive reminders during shopping trips - Kulkarni, Atul; Wang, Xin Cindy; Yuan, Hong (Journal of Consumer Marketing, 2019)
Purpose This paper aims to examine the unintended negative effect of incentivizing shoppers to make unplanned purchases through incentive reminders during shopping trips. Design/methodology/approach Two experimental studies with between-subject designs were conducted to examine the effect of incentive reminders and related factors on abandonment intention. Findings When the search for unplanned purchases needed to reach promotional threshold fails, shoppers’ propensity to abandon a transaction increases if they are reminded of an incentive during their shopping trip. When the size of the planned purchases is relatively larger than the incentivized unplanned purchases, abandonment propensity is higher in response to reward type incentives, whereas when the size of the planned purchases is relatively smaller than the incentivized unplanned purchases, abandonment propensity is higher in response to avoidance type incentives. Research limitations/implications This research intersects and integrates several research domains, specifically transaction abandonment, promotional reactance, unplanned purchases and promotion framing. Practical implications Findings from this research help managers understand the possible negative consequences of incentive reminders and offer suggestions for decreasing shopper propensities to abandon transactions in response to incentive reminders aimed at increasing transaction sizes. Originality/value This is the first study to highlight (i) the possible effect of incentive reminders on transaction abandonment; (ii) the influence of the size of unplanned purchases and incentive types on abandonment; and (iii) the underlying roles of perceived value of planned purchases and fairness perceptions in abandonment.
Keywords: Incentive reminders; Promotional reactance; Transaction abandonment; dept.mrk; peer-reviewed